Leaarning Video Media with Student Learning Outcomes for Continental Subjects - Febrianti, Windi Mulya; Andriani, Cici; Gusnita, Wiwik; Indrayeni, Wiwik; Sari, Yolanda Intan (Universitas Negeri Padang, 2025)
This research is motivated by the level of student interest in video learning media which is relatively high but student learning outcomes have not yet reached the maximum limit, therefore this research aims to describe video learning media, describe student learning outcomes and analyze the relationship between video learning media and learning outcomes. class XI Culinary student at SMK Negeri 2 Pariaman. The type of research used is quantitative with a correlational approach. The research sample consisted of 63 students, with 31 students XI Culinary 1 and 32 students XI Culinary 2. Data collection techniques included questionnaires and tests that had been tested for validity and reliability. Data were analyzed using descriptive and correlation analysis. The results of the hypothesis t-test show that student learning outcomes have a tcount value of 3.917 > ttable -1.6702 or sig. (2- tailed) 0.00 < 0.05. Thus, Ho is rejected and Ha is accepted, which means there is a positive and significant relationship between video learning media and student learning outcomes on continental menu material..